Unleash your complexity genius : growing your inner capacity to lead - Berger, Jennifer Garvey, 1970-; Coughlin, Carolyn (Stanford Briefs, an imprint of Stanford University Press, 2023)
There is a complexity paradox that we all need to understand. We humans have a natural inclination towards connection, engagement, and creativity -- all necessary skills to thrive in complexity. The problem is that the stress caused by uncertainty and ambiguity makes it difficult to tap into this inclination when we need it the most. This book offers a set of practices that help you not only understand complexity but actually hack into your own nervous system to bring your natural capacities back online. By paying close attention to your body, redefining your emotional experiences, and connecting more deeply to others, you can transform the anxiety, exhaustion, and overwhelm that complexity creates. Better still, as you unleash your natural complexity genius, you create the conditions for those around you to flourish in an uncertain world.--